Non-invasive ultrasonic examination of the local pulse wave velocity in the common carotid artery - Powałowski, T.; Trawiński, Z. (Archives of Acoustics, 2004)
Local pulse wave velocity (PWV) is one of important indicators of artery wall's elastic properties. This paper describes a non-invasive method of examinations of local PWV on the basis of ultrasonic blood flow velocity measurements at two points, several centimetres along the common carotid artery (CCA). This velocity was compared with values of PWV calculated on the basis of measurement of distensibility coefficient DC. The examinations were carried out on the group of 12 healthy volunteers ranging in age from 22 to 68 years (mean 39[ampersand]plusmn;16 years). Mean value of local PWV for the examined group was 5.1[ampersand]plusmn;1.09 m/s. This velocity was linearly correlated (r = 0.9807) with the PWV examined on the basis of distensibility coefficient DC, the mean value of which was 6.14[ampersand]plusmn;1.29 m/s.